PENGEMBANGAN MEDIA PETA TEMATIK DENGAN MATERI SEJARAH LOKAL ALUN-ALUN KOTA DI SMAN 1 TUBAN - Khakim, Mochammad Nurfahrul Lukmanul; Primanggalang, Kautsar Ranggi; Yuliati, Yuliati; Surya, Riza Afita (Universitas Negeri Malang, 2022)
This research begins by looking at the learning problems that occur in class XI IPS 1 at SMAN Tuban, namely the lack of motivation and student learning outcomes, then conducting a needs analysis and selecting media development according to the problems that occur. The thematic map media development that utilizes the Google Maps application uses a development model from Lee & Owen. The results of the validation show: 1) Material validator with a percentage of 85.41 percent with